Analisis Strategi Pemasaran Pembiayaan Kendaraan Dalam Meningkatkan Jumlah Nasabah Pada PT. Bank Syariah Indonesia KCP Stabat - Melinda Melinda; Abdullah Sani; Muhammad Arfan Harahap (Yayasan Rahmat Islamiyah, 2022)
This research aims to find out the marketing strategy of vehicle financing in increasing the number of customers at PT. Bank Syariah Indonesia KCP Stabat. The research method used is a qualitative research method that is descriptive with an empirical approach. The results of the study explained that the mechanisms and procedures for vehicle financing in PT. Bank Syariah Indonesia KCP Stabat begins with the submission of proposals / files, investigation of files, approval of financing and signing of financing contracts, after that the Bank makes a purchase order (PO) to the dealer / showroom that contains specifications according to the customer's wishes and prepares all documents needed for the disbursement of financing by the Bank and installment payments in accordance with the agreement. Marketing strategy implemented by PT. Bank Syariah Indonesia KCP Stabat in increasing motor vehicle financing refers to the marketing mix, namely products, prices, distribution / place, and promotion. The results of the SWOT analysis are the strengths of its implementation in accordance with sharia, light down payment, low margins, long installment periods and free of penalty fees, in addition to a strategic location. Weakness is the lack of knowledge of the community. Opportunities are the high interest of the public to buy a vehicle and the increasingly fanatical Muslims with their religion. Threats are the proliferation of financial institutions such as leasing that do focus on purchasing vehicles and the public is more interested in applying for purchases to leasing.